A Randomized Clinical Trial Comparing Individual Cognitive Behavioral Therapy and Child-Centered Therapy for Child Anxiety Disorders. Issue 4 (4th July 2018) - Silk, Jennifer S.; Tan, Patricia Z.; Ladouceur, Cecile D.; Meller, Suzanne; Siegle, Greg J.; McMakin, Dana L.; Forbes, Erika E.; Dahl, Ronald E.; Kendall, Philip C.; Mannarino, Anthony; Ryan, Neal D.
Abstract : This study compared individual cognitive behavioral therapy (CBT) and a supportive child-centered therapy (CCT) for child anxiety disorders on rates of treatment response and recovery at posttreatment and 1-year follow-up, as well as on real-world measures of emotional functioning. Youth ( N = 133; ages 9–14) with anxiety disorders (generalized, separation, and/or social anxiety) were randomized using a 2:1 ratio to CBT ( n = 90) or CCT ( n = 43), which served as an active comparison. Treatment response and recovery at posttreatment and 1-year follow-up were assessed by Independent Evaluators, and youth completed ecological momentary assessment of daily emotions throughout treatment. The majority of youth in both CBT and CCT were classified as treatment responders (71.1% for CBT, 55.8% for CCT), but youth treated with CBT were significantly more likely to fully recover, no longer meeting diagnostic criteria for any of the targeted anxiety disorders and no longer showing residual symptoms (66.7% for CBT vs. 46.5% for CCT). Youth treated with CBT also reported significantly lower negative emotions associated with recent negative events experienced in daily life during the latter stages of treatment relative to youth treated with CCT. Furthermore, a significantly higher percentage of youth treated with CBT compared to CCT were in recovery at 1-year follow-up (82.2% for CBT vs. 65.1% for CCT). These findings indicate potential benefits of CBT above and beyond supportive therapy on the breadth, generalizability, and durability of treatment-related gains.